Marginal sinus placenta previa is a different entity in placenta previa: A retrospective study using magnetic resonance imaging - Hiroki Ishibashi; Morikazu Miyamoto; Hiroaki Soyama; Hiroshi Shinmoto; Wakana Murakami; Masaya Nakatsuka; Takahiro Natsuyama; Masashi Takano; Masashi Yoshida; Kenichi Furuya (Elsevier, 2018)
Objective: The current definition of placenta previa does not include whether the placental edge is parenchyma or marginal sinus defined as placenta previa in which the placental marginal sinus just reached the internal os and/or in which the placental parenchyma might be located at > 2 cm from internal os. Materials and Methods: Cases with placenta previa were identified through the review of magnetic resonance imaging (MRI) from among 210 cases at our institution between 2007 and 2016. The clinical outcomes of patients with marginal sinus placenta previa (Group A) were compared with patients with low-lying placenta and marginal placenta (Group B) and patients with partial placenta and total placenta previa (Group C), respectively. This study was a retrospective analysis. Results: Twenty-seven (12.7%) cases were included in Group A. The patients in Group B and Group C were 72 and 108 cases, respectively. First, Group A more frequently underwent emergency cesarean section than Group B (p = 0.02). There was no statistical significance with other maternal history, post-or pre-operative hemorrhage, and/or additional treatment for hemorrhage between the two groups. Additionally, Group A delivered at a later gestational age (p < 0.01); were less frequently complicated with antenatal bleeding (p < 0.01); underwent emergency cesarean section (p < 0.01), allogenic blood transfusion (p < 0.01), and uterine artery embolization (p < 0.01) for postpartum hemorrhage less often; and had less perioperative hemorrhage (p < 0.01) than Group C. Conclusions: Marginal sinus placenta previa may be a mild type of placenta previa. This new classification could be useful in the management of placenta previa. Keywords: Placenta previa, Magnetic resonance imaging, Marginal sinus placenta previa, Hemorrhage